Ceramic pigments and dyes beyond the inkjet revolution: From technological requirements to constraints in colorant design. Issue 14 (1st October 2020) - Molinari, C.; Conte, S.; Zanelli, C.; Ardit, M.; Cruciani, G.; Dondi, M.
Abstract: The advent of digital decoration has changed the technological requirements of colorants and the way they are applied onto ceramic substrates. This technological revolution has introduced additional steps in colorant production (ink micronization) and new constraints in application (ink-jet printing) that cannot be reproduced in a standard ceramic laboratory, so stretching the distance between academic and industrial research. The goal of this work is to provide an up-to-date picture of ceramic pigments, dyes and effects, with emphasis on their behavior in the current decoration technologies, which are shortly reviewed. Technological performance expected for ceramic colorants and new requirements imposed by digital decoration are discussed in detail. An extensive overview of both industrially used and candidate pigments, dyes and effects is focused on the suitability to different ceramic applications and firing conditions. Finally, lines of future research are outlined and commented.